2009
DOI: 10.1523/jneurosci.2339-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Mediates Proteolysis of the Voltage-Gated Sodium Channel α-Subunit

Abstract: Alterations in the expression, molecular composition, and localization of voltage-gated sodium channels play major roles in a broad range of neurological disorders. Recent evidence identifies sodium channel proteolysis as a key early event after ischemia and traumatic brain injury, further expanding the role of the sodium channel in neurological diseases. In this study, we investigate the protease responsible for proteolytic cleavage of voltage-gated sodium channels (NaChs). NaCh proteolysis occurs after prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 26 publications
(32 reference statements)
3
94
0
Order By: Relevance
“…33,96 In addition, proteolysis of the sodium channel inactivation gate by calcium activated protease, calpain, was found to lead to persistent increases in intra-axonal calcium. 160 Release of intra-axonal calcium stores after injury has also been observed. 98 These effects represent potential therapeutic targets using agents that block sodium channels, calcium channels, and sodium-calcium exchangers or by calpain inhibition as described below.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…33,96 In addition, proteolysis of the sodium channel inactivation gate by calcium activated protease, calpain, was found to lead to persistent increases in intra-axonal calcium. 160 Release of intra-axonal calcium stores after injury has also been observed. 98 These effects represent potential therapeutic targets using agents that block sodium channels, calcium channels, and sodium-calcium exchangers or by calpain inhibition as described below.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…These include ␣II-spectrin (Siman et al, 1984;Nixon, 1986), actin (Villa et al, 1998), glutamate receptors (Bi et al, 1997;Xu et al, 2007), the postsynaptic density-95 protein (Gascó n et al, 2008), the Na ϩ /Ca 2ϩ exchanger (Bano et al, 2005), ankyrinG (Schafer et al, 2009), the voltage-gated sodium channel ␣ subunit (von Reyn et al, 2009), and the plasma membrane Ca 2ϩ -ATPase (Pottorf et al, 2006). However, whether calpain plays a role in neuronal Cl Ϫ regulation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…25 These results were further confirmed by von Reyn and colleagues, that calpain-mediated proteolysis of the sodium channel a subunit within the I -II and III-IV loops of Na v 1.2; however, the authors indicated that sites of proteolysis might differ between a subunit. 26 Their further study reported that calpain activation and subsequent proteolysis of sodium channel a subunit were mediated by NMDA receptors and sodium channels following stretch injury. 27 A recent in vivo study employed a novel calpastain overexpressing transgenic mouse model and demonstrated that augmenting calpastatin levels attenuated calpain-mediated proteolysis of sodium channels.…”
Section: Discussionmentioning
confidence: 99%